2020
DOI: 10.1111/ipd.12663
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between viral load, CD4 count, WHO staging, and dental caries in HIV‐positive children?

Abstract: Background Few studies have investigated an association between CD4 counts, viral load (VL), WHO staging, and caries among HIV‐positive (HIV+) children on HAART therapy (>12 months). Aim To determine the strength of association between CD4 counts, WHO staging, VL, and dental caries. Design This cross‐sectional analytical study comprised of 355 HIV + children, aged 4‐12 years, attending a hospital in Johannesburg, South Africa. Demographic and clinical data such as decayed (d,D), missing (m,M), filled teeth (f,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A study that shows an association between viral load and patient satisfaction is spared. However, evidence revealed a significant inverse association between viral load and CD4 count: low viral loads were associated with higher CD4 counts [36] and higher CD4 counts and satisfaction [16]. Moreover, male caregivers had higher odds of satisfaction with ART service than female caregivers.…”
Section: Plos Onementioning
confidence: 96%
“…A study that shows an association between viral load and patient satisfaction is spared. However, evidence revealed a significant inverse association between viral load and CD4 count: low viral loads were associated with higher CD4 counts [36] and higher CD4 counts and satisfaction [16]. Moreover, male caregivers had higher odds of satisfaction with ART service than female caregivers.…”
Section: Plos Onementioning
confidence: 96%
“…An association between CD4+ count and the presence of oral lesions has been demonstrated in the literature (78,79). However, Yengopal et al (80) found no substantial evidence of a significant association between the presence of dental caries among HIV-positive children and CD4 counts and viral load, meaning that a more robust trial to gain new scientific evidence is needed to ascertain the linkage between oral diseases and CD4+ count in HIV-infected children.…”
Section: Problems Affecting Feeding Practices Among Hiv-infected Infants and Childrenmentioning
confidence: 99%